Level-shift space vector pulse width modulation for a nine-switch inverter - Neerakorn Jarutus (2018)
© 2015 IEEE. This paper presents a nine-switch inverter using a level-shift carrier-based space vector pulse width modulation (SVPWM) scheme, controlling the two paralleled ac loads for constant frequency mode (CF-mode) and variable frequency mode (VF-mode) without the short-through in the inverter leg. The dual output voltages and phase currents can be kept out of the distorted attribute, which is produced by the crossover of the modulating signals. The mathematical models are proposed by the SVPWM scheme and based on the zero-sequence injection principle. The shifted levels of the SVPWM modulating signals with the offset control decrement are then designed by the relationship of the modulation indices. The proposed modulation performance has been verified by the simulated implementation that is effectively carried out on the applicability of the proposed algorithm, the high modulation index is needed.